Kako dolgo čakamo na avtobus v Cuernavaci? - Pirnat, Anja (Matrika, 2019)
Random matrix theory (RMT) aims to provide understanding of diverse properties, mainly statistics of matrix eigenvalues of large matrices with entries drawn randomly from various probability distributions traditionally referred to as the random matrix ensembles. Three classical random matrix ensembles are the Gaussian Orthogonal Ensemble (GOE), the Gaussian Unitary Ensemble (GUE) and the Gaussian Symplectic Ensemble (GSE). RMT has found applications in various branches of physics and mathematics; for instance, fluctuations in positions of compound nuclei resonances, distribution of zeros of the Riemann zeta function and also spacings between two subsequent buses in Cuernavaca are well described by the RMT statistics.
Keywords: ansambel naključnih matrik; fluctuations in positions of compound nuclei resonances; naključne matrike; random matrices; random matrix ensembles; razmiki pozicij nevtronskih resonanc; statistics; statistika